2007
DOI: 10.5194/angeo-25-1337-2007
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of plasma density in the topside ionosphere on the solar activity level

Abstract: Abstract. In this paper, the ten-year (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) total ion density N i measurements from the Defense Meteorological Satellite Program (DMSP) spacecraft in the morning and evening (09:30 and 21:30 LT) sectors have been analyzed to explore the dependence of plasma densities in the topside ionosphere at middle and low latitudes on the solar activity level. Results indicate that there is a strong solar activity dependence of DMSP N i at 848 km altitude, which has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 30 publications
1
54
1
Order By: Relevance
“…The former shows an amplification feature [75]. Moreover, the seasonal variation of the plasma density at 800 km is dominated by the annual component.…”
Section: Features At Different Altitudesmentioning
confidence: 94%
See 2 more Smart Citations
“…The former shows an amplification feature [75]. Moreover, the seasonal variation of the plasma density at 800 km is dominated by the annual component.…”
Section: Features At Different Altitudesmentioning
confidence: 94%
“…Zhao et al [74] examined the seasonal and solar activity variations of the plasma compositions at 800 km and developed an empirical model for the DMSP plasma density using empirical orthogonal functions. Liu et al [75,76] further studied the topside plasma density of the DMSP observations and found interesting climatological features: in the topside ionosphere there is strong annual asymmetry in the yearly variations, and an amplification effect in the solar activity dependence of the plasma density was reported for the first time.…”
Section: Features At Different Altitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works showed the nonlinearity appearing in the variations of the ionospheric electron density with solar indices [e.g., Balan et al, 1994aBalan et al, , 1996Belehaki et al, 2001;Chen et al, 2008Chen et al, , 2009Gupta and Singh, 2000;Kouris et al, 1998;Liu et al, 2003Liu et al, , 2004aLiu et al, , 2006Liu et al, , 2007Liu and Chen, 2009;Ma et al, 2009;Park et al, 2008;Richards, 2001;Sethi et al, 2002;Su et al, 1999]. An important nonlinear character is the saturation effect that was found in the variations of N m F 2 (maximum electron density of the F 2 layer) or TEC (total electron content) with solar indices; namely, N m F 2 (TEC) increases linearly with solar indices with a higher rate at lower solar activity levels, whereas the increase rate decreases, or even N m F 2 (TEC) does not obviously increase, at higher solar activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…The diurnal variation of solar activity effect on daily NmF2 and hmF2 measured over Dibrugarh and Okinawa from August 2010 till July 2014 and its seasonal variation is studied using solar activity proxies. The widely reported non-linear variation of NmF2 with solar activity (Bhuyan et al 1983;Balan et al 1993Balan et al , 1994Liu et al 2006Liu et al , 2007a is shown to exhibit a diurnal variation. The correlation of Dibrugarh NmF2 and hmF2 with solar activity as well as EEJ is compared with that of Okinawa.…”
Section: Introductionmentioning
confidence: 99%